Painting - The Art of Color - Hapov Vasiliy Nikolayevich (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article, the author describes the possibilities of color and impression, the main idea of the composition through color, the complex world of human emotions and character, the techniques, methods and materials used in painting, as well as the types of painting and the history of painting, additionally also reveals the freedom and full power and color necessary for the artist in the painting to highlight the main idea of the composition, to emphasize the important details, to give the depth of the distance or to give the image flatness, and also it should be noted that the author also pointed out that the image of form and distance, images and movements, which are the most important distinguishing features of painting, can only be seen through color.